Short- and medium-term effect of inhaled corticosteroids on exhaled breath biomarkers in severe asthma. (1st October 2022) - Alahmadi, Fahad H; Wilkinson, Max; Keevil, Brian; Niven, Rob; Fowler, Stephen J
Abstract: Inhaled corticosteroids (ICS) are the mainstay of therapy in asthma, but benefits vary due to disease heterogeneity. Steroid insensitivity is a particular problem in severe asthma, where patients may require systemic corticosteroids and/or biologics. Biomarkers sensitive to ICS over a short period of time could inform earlier and more personalised treatment choices. To investigate how exhaled breath biomarkers change over two-hours and one-week following monitored ICS dosing in severe asthma patients with evidence of uncontrolled airway inflammation. Patients with severe asthma and elevated fractional exhaled nitric oxide (FeNO) (⩾45 ppb, indicative of active airway inflammation) were recruited. Exhaled breath biomarkers were evaluated using (FeNO), exhaled breath temperature (EBT), particles in exhaled air (PExA) and volatile organic compounds (VOCs). Samples were collected over 2 h following observed inhalation of 1000 mcg fluticasone propionate, and at a second visit 1 week after taking the same dose daily via an inhaler monitoring device that recorded correct actuation and inhalation. Changes in parameters over 2 h were analysed by the Friedman test and 1 week by Wilcoxon's test ( p -value for significance set at 0.05; for VOCs false discovery rate q of 0.1 by Benjamini–Hochberg method applied). 17 participants (9 male) were recruited, but three could not complete PExA and two FeNO testing, as they were unable to comply with the necessary technique; complete datasets were available from 12 (9 male) with median (interquartile range) age 45 (36–59) yrs. EBT ( p < 0.05) and levels of six VOCs ( q < 0.1) fell over the 2 h after high dose ICS; there were no changes in FeNO or PExA. After one week of using high dose ICS, there were falls in FeNO, EBT and two VOCs ( p < 0.05), but no changes in PExA. Reduction in EBT over the short and medium term after high dose ICS may reflect airway vascular changes, and this, together with the observed changes in exhaled VOCs, merits further investigation as potential markers of ICS use and effectiveness.